2018
DOI: 10.1186/s13046-018-0793-4
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs in ovarian cancer

Abstract: Long non-coding RNAs (lncRNAs) refer to functional cellular RNAs molecules longer than 200 nucleotides in length. Unlike microRNAs, which have been widely studied, little is known about the enigmatic role of lncRNAs. However, lncRNAs have motivated extensively attention in the past few years and are emerging as potentially important regulators in pathological processes, including in cancer. We now understand that lncRNAs play role in cancer through their interactions with DNA, protein, and RNA in many instance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 114 publications
0
73
0
Order By: Relevance
“…To further understand the role of this CAM in regulating cancer metastasis, other future experiments may include: (a) searching for the heterophilic ligands or partners of METCAM/MUC18 [ 9 ], (b) systematic investigation of the three mechanisms in the tumor and metastasis dormancy (for examples, what are the key members involved in intrinsic growth inhibition, immunological suppression, and/or reducing angiogenesis?) [ 41 ], (c) possible miRNAs [ 42 ] and long non-coding RNAs [ 43 ] upstream and downstream of METCAM/MUC18 involved in the process and (d) the transcriptional control in the processes [ 9 ]. Precaution should be taken that a complete picture may only be possibly constructed after all the above studies are successfully executed.…”
Section: Discussionmentioning
confidence: 99%
“…To further understand the role of this CAM in regulating cancer metastasis, other future experiments may include: (a) searching for the heterophilic ligands or partners of METCAM/MUC18 [ 9 ], (b) systematic investigation of the three mechanisms in the tumor and metastasis dormancy (for examples, what are the key members involved in intrinsic growth inhibition, immunological suppression, and/or reducing angiogenesis?) [ 41 ], (c) possible miRNAs [ 42 ] and long non-coding RNAs [ 43 ] upstream and downstream of METCAM/MUC18 involved in the process and (d) the transcriptional control in the processes [ 9 ]. Precaution should be taken that a complete picture may only be possibly constructed after all the above studies are successfully executed.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer is regarded as the most lethal gynecological cancer among the female population worldwide, and the role of lncRNAs in ovarian cancer has been well characterized. [20][21][22] In the current study, we unraveled the function of a novel lncRNA, TMPO-AS1, in ovarian cancer, which has not been discussed previously to our knowledge. We demonstrated that lncRNA TMPO-AS1 played an oncogenic role in ovarian cancer.…”
Section: Discussionmentioning
confidence: 87%
“…Differential expression between tumor and non-tumor tissue at this gene has been founded in lung cancer [39] and ovarian cancer [40]. Anyhow, functional validation studies are needed to explore the mechanisms of the potential roles of these genes in risk of HBV-related HCC.…”
Section: Discussionmentioning
confidence: 99%